Effect of environment and technology in the effectiveness of information system project selection through the user acceptance - Syaifudin; Abdullah, Che Sobry; Mohamed Udin, Zulkifli; Hassan, Mohamad Ghozali; Johari, Nor Azmi (2011)
At present the information system project selection is difficult because many factors that influence it. Technology, environment and user acceptance influence to the information system project selection. The purpose of this paper is how big the influence of technology, environment and user acceptance of information systems project selection effectively and efficiently. This research was conducted by searching the sample data in the ministries and analyzed using SEM.The results of this research is that technology and the environment affect user acceptance. Besides, technology and environment influence the effectiveness of information system project selection through the user acceptance mediators.